2017
DOI: 10.3389/fpls.2017.00780
|View full text |Cite
|
Sign up to set email alerts
|

Drawing Links from Transcriptome to Metabolites: The Evolution of Aroma in the Ripening Berry of Moscato Bianco (Vitis vinifera L.)

Abstract: Monoterpenes confer typical floral notes to “Muscat” grapevine varieties and, to a lesser extent, to other aromatic non-Muscat varieties. Previous studies have led to the identification and functional characterization of some enzymes and genes in this pathway. However, the underlying genetic map is still far from being complete. For example, the specific steps of monoterpene metabolism and its regulation are largely unknown. With the aim of identifying new candidates for the missing links, we applied an integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 130 publications
(161 reference statements)
0
32
0
Order By: Relevance
“…Secondary metabolites play an essential role in plant defense system and development processes [14][15][16]. The accumulation of secondary metabolites can be influenced by environmental factors and different plant growth stages [17][18][19][20]. Previous studies have reported that the metabolites of green tea (C. sinensis) varied according to geography, developmental stages, and cultivars [2,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites play an essential role in plant defense system and development processes [14][15][16]. The accumulation of secondary metabolites can be influenced by environmental factors and different plant growth stages [17][18][19][20]. Previous studies have reported that the metabolites of green tea (C. sinensis) varied according to geography, developmental stages, and cultivars [2,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the analysis of additional metabolites (e.g., carotenoids and chlorophylls) could point out potentially competing reactions. The involvement of multiple key enzymes might also explain the lack of linalool in the microvines under investigation; in particular, terpene synthases or other genes in the confidence interval of the previously identified linalool-specific QTL on chromosome 10 (Battilana et al, 2009 ; Emanuelli et al, 2011 ; Costantini et al, 2017 ) might play a limiting role in linalool production in combination with VvDXS1 , as highlighted in the grapevine germplasm (Figures 5C,D ) and reported in other plants (Zeng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the expression of the CYP76 family was mostly upregulated in grapevine flowers, similarly to what Boachon and coworkers [ 21 ] found in Arabidopsis . Interestingly, grapevine flowers, just like berries, are very rich in terpenes, some of the most important volatile compounds contributing to the floral bouquet of wine [ 75 , 83 , 84 ] and CYP76s were already found to be involved in terpene biosynthesis in Arabidopsis and grapevine [ 21 , 31 , 85 , 86 ]. More, CYP76 family showed the greatest number of genes with varietal-specific expression patterns during berry development.…”
Section: Discussionmentioning
confidence: 99%